Surgical techniques to reduce oronasal fistula risk in wide cleft palate repair: a systematic review (Medical Journal of Indonesia, 2022)
BACKGROUND Wide cleft palate is a common congenital anomaly, particularly in developing countries with limited access to plastic surgeons and specialized cleft centers. It can be severe and may contribute to the development of oronasal fistula, which can occur in up to 78% of cases. Despite numerous surgical techniques for wide cleft repair, the best method remains unclear. This study aimed to identify surgical techniques for wide cleft palate repair to minimize the occurrence of oronasal fistula. METHODS Literature searching was conducted using multiple online databases including PubMed, Scopus, and Cochrane Library. The keywords used were “cleft palate”, ” surgery”, “technique”, “palatoplasty”, and “wide”. Inclusion and exclusion criteria were applied to select relevant studies, and the quality was assessed. RESULTS A total of 12 studies discussed surgical techniques to repair the primary wide cleft palate and their outcome on oronasal fistula formation. The surgical techniques included modified Furlow palatoplasty, two-flap palatoplasty, and modified Bardach’s two-flap palatoplasty. The incidence of oronasal fistula was 9.6% (n = 28/291) in one-stage Furlow palatoplasty and 12.0% (n = 24/200) in the modified one-stage two-flap palatoplasty. CONCLUSIONS Two-flap palatoplasty and Furlow palatoplasty (and their modifications) were the safe surgical techniques for wide cleft repair with a low occurrence of oronasal fistula.